A Functional SMAD2/3 Binding Site in the PEX11β Promoter Identifies a Role for TGFβ in Peroxisome Proliferation in Humans - Azadi, Afsoon S.; Carmichael, Ruth E.; Kovacs, Werner J.; Koster, Janet; Kors, Suzan; Waterham, Hans R.; Schrader, Michael (Frontiers in Cell and Developmental Biology, 2020)
In mammals, peroxisomes perform crucial functions in cellular metabolism, signalling and viral defense which are essential to the viability of the organism. Molecular cues triggered by changes in the cellular environment induce a dynamic response in peroxisomes, which manifests itself as a change in peroxisome number, altered enzyme levels and adaptations to the peroxisomal morphology. How the regulation of this process is integrated into the cell’s response to different stimuli, including the signalling pathways and factors involved, remains unclear. Here, a cell-based peroxisome proliferation assay has been applied to investigate the ability of different stimuli to induce peroxisome proliferation. We determined that serum stimulation, long-chain fatty acid supplementation and TGFβ application all increase peroxisome elongation, a prerequisite for proliferation. Time-resolved mRNA expression during the peroxisome proliferation cycle revealed a number of peroxins whose expression correlated with peroxisome elongation, including the β isoform of PEX11, but not the α or γ isoforms. An initial map of putative regulatory motif sites in the respective promoters showed a difference between binding sites in PEX11α and PEX11β, suggesting that these genes may be regulated by distinct pathways. A functional SMAD2/3 binding site in PEX11β points to the involvement of the TGFβ signalling pathway in expression of this gene and thus peroxisome proliferation/dynamics in humans.